Application of cost of capital for capital structuring in Croatian firms - Silvije Orsag; Josip Mitar (UTMS Journal of Economics, 2014)
This paper show result of empirical analysis application of cost of capital for capital structuring in Croatian firms. Intensity of this applications is highly unrespectable because Croatian firms usually calculated cost of capital in their capital budgeting process. Analysis also show low inconsistency of Croatian firm's capital structures with peaking order theory. The paper shows that Croatian firm's employ debt in their capital structure close to the debt equity ratio 1:1, with the significant portion of trade credit and short term bank credits. This short term liabilities are greater than 60% of total used debt in analyzing firms. Finally, paper shows that with degree of using the cost of capital in capital structuring rise profitability of analyzing firms.
Keywords: G32; 330; cost of capital; capital structure; profitability; leverage